2013
DOI: 10.1097/00001416-201301000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Educational Perspectives and Teaching Styles of Faculty Who Lead International Service-Learning Experiences

Abstract: Background and Purpose: Many physical therapy educational programs are adding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…This could start from faculty recruitment by inquiring into how their values, teaching approaches, and educational perspectives align with institutional and professional SR agenda as those will serve as framework for their teaching practices. 57 Employed educators' continued socialization into the institution's culture of SR and strategic professional development could further support working with students on developing SR. For example, some participants recognized the need for upskilling on mentoring students toward becoming socially responsible. Educators may also need support in implementing a curriculum that balances achievement of graduate outcomes with autonomous, transformative learning through praxis.…”
Section: Discussionmentioning
confidence: 99%
“…This could start from faculty recruitment by inquiring into how their values, teaching approaches, and educational perspectives align with institutional and professional SR agenda as those will serve as framework for their teaching practices. 57 Employed educators' continued socialization into the institution's culture of SR and strategic professional development could further support working with students on developing SR. For example, some participants recognized the need for upskilling on mentoring students toward becoming socially responsible. Educators may also need support in implementing a curriculum that balances achievement of graduate outcomes with autonomous, transformative learning through praxis.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of service-learning by Seifer, 31 though originally framed with a local community focus, has been used to define service-learning in an international context. 1,3,14,32 Specifically, Seifer defines service-learning as “a structured learning experience that combines community service with explicit learning objectives, preparation and reflection.” 31(p.274) The work by Seifer 31 emphasizes a collaborative model in which the community's needs drive the structure of the experience, and community organizations are integral partners in the equation. This learning model was launched to provide college and university students with a “local community context” to connect their academic preparation with their civic roles in tangible ways.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Due to higher education institutions becoming so widely diverse, educators should immerse themselves in professional development activities that can help frame teaching techniques that are effective to all students. Audette and Roush (2013) accentuated that faculty who tie educational theories to their teaching seem to have more structure and meaning in their academic delivery, positively affecting student outcomes, evaluations, and relationships [19]. Conversely, Redden (2017) reported that faculty or professional development workshops were only being offered by a quarter of institutions in American [20].…”
Section: Faculty Development Strategiesmentioning
confidence: 99%